Cat Who Talked to Ghosts Lilian Jackson Braun - Braun, Lilian Jackson (G. P. Putnam's Sons, 1990)
When Iris Cobb, who claimed ghosts were haunting the farmhouse museum, dies under mysterious circumstances, Jim Qwilleran decides to investigate
Keywords: Cozy Animal Mysteries; Short Stories & Anthologies; American Literature